Peran Motivasi Kerja dalam Meningkatkan Kinerja Karyawan di LKP Bahana Bina Prestasi Ponorogo - Kevin Isa Zahroni; Dwi Setya Nugrahini (Institut Agama Islam Negeri Ponorogo, 2023)
Work motivation is a form of drive within an individual to complete a task. According to Herzberg's Two-Factor Theory, work motivation consists of two components: external factors and internal factors. In courses and training institutes Bahana Bina Prestasi, work motivation seems lacking, which contradicts the efforts made by the institution's leaders who provide regular work motivation in monthly briefings. This research aims to determine work motivation's role in improving employee performance at LKP Bahana Bina Prestasi in Ponorogo. This research utilizes a qualitative descriptive research method. Data sources include employees, business owners, or leaders at LKP Bahana Bina Prestasi in Ponorogo. Data collection techniques involve conducting interviews. This research indicates that the factors causing a decrease in work motivation lie in external factors, such as salary and quality of supervision. However, there are strengths in working conditions, interpersonal relationships, achievements, recognition, the job itself, and responsibility. Additionally, the implementation of work motivation in LKP Bahana Bina Prestasi is considered to be less than ideal because, despite being conducted regularly, it is not yet considered good and effective. Out of the five performance indicators, this institution has successfully implemented two indicators, namely Quality and Timeliness. However, three areas still need improvement: Quantity, Effectiveness, and Efficiency.